"Se o mestre não tiver firmação ele vai a nado" : o Jongo de São Bartolomeu no norte capixaba - Siqueira, Jane Seviriano (2017)
Nowadays, forms of expression of identity in black-people groups, such as those found in southeastern Brazil, have gained highlighted. The present work analyzes the way in which people of the north of the state of Espirito Santo express their identity through devotion to Sao Bartolomeu (St. Bartholomeu). For this purpose, fieldwork was carried out in the Santana neighborhood, which is located in the municipality of Conceicao da Barra, in the north of the Espírito Santo (or norte capixaba). A set of interviews were conducted for collecting stories of the devout people. Such stories were confronted with information of previous works related to clustering of black people in the norte capixaba. It was found that the identity categories of black-people in the Santana are elaborated by means of a set of religious practices that elect devotion to the saint, of which the São Bartolomeu’s Jongo, a group that congregates more people in Santana, stands out. Also, it has been found the processions and narratives related to the saint are important in the elaborations around the categories of identification. These results indicate that there is a great influence of the devotional practices in the build-up around the identity in this group. For instance, currently the São Bartolomeu’s Jongo is an important group in the Espírito Santo and became a cultural patrimony of the northern region of this state.